Exotic neutron-rich nuclei in a three-body model - Tomio, L. [UNESP] (2007)
We present results for spatial distributions of weakly-bound three-body systems, derived from a universal scaling function that depends on the mass ratio of the particles, as well as on the nature of the subsystems. © 2007 American Institute of Physics.